The Contribution of Dr. Roy Warren Sweat's Atlas Orthogonal Technique to Chiropractic. - GOLEMBIEWSKI, GARY V. (Chiropractic History)
With the passing of Roy W. Sweat, D.C., B.C.A.O., on January 2, 2022, the chiropractic world lost an iconic figure; however, the vision of chiropractic as taught by the founder of the Atlas Orthogonal Technique (AOT) will live on. In a plan to maintain and promote his vision, a board of fifteen practicing, board-certified Atlas Orthogonal doctors was established. They are responsible for creating and enforcing protocols for AOT practices, overseeing chiropractic colleges that teach the technique, and supporting chiropractic research that will benefit patients' health now and in the future. Dr. Sweat left behind a strong base that will continue to improve chiropractic outcomes by searching for more effective ways to adjust the atlas vertebra. This is his legacy and gift to us all. Below you will read how his vision became a reality.